(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
Fibromyalgia Tender Points (FMTPs) and functional health status measured by Health Assessment Questionnaire (HAQ) as well as health related quality of life by short form-36 (SF-36) in Systemic Lupus Erythematosus (SLE) patients have integrated adherent to each other. Comparison of fibromyalgia tender points and health status in many studies revealed remarkable correlation in both chronic rheumatologic diseases. We observed higher HAQ score and significant positive correlation between FMTP and HAQ score and we also found significant negative correlation in almost all domains of SF-36 with FMTP in SLE patients. Therefore, reduced functional status was found in SLE patients with higher FMTP count. To determine influence of the number of fibromyalgia tender points on functional health status as well as health related quality of life in SLE patients. The observational study carried out enrolling 67 female SLE patients and equal number of asymptomatic female subjects in Lupus Clinic of Rheumatology Wing, BSMMU, Dhaka from April 2005 to October 2006.After fulfilling the inclusion criteria with a detailed history and thorough physical examinations, obtained data were recorded in a pro-forma. 18 FMTP sites and 6 control sites were examined. Positive FMTP scores were recorded in a body chart. Culturally adopted and validated Bengali version of HAQ and SF-36 were filled-up to assess the self-reported health status. Both of the SLE patients and control subjects were classified into two subgroups. 0-10 FMTP’ group and > 11 FMTP group. The HAQ score (Mean + SD) of SLE patients and of controls were 0.54 + 0.54 and 0.17 + 0.25 respectively. The difference was statistically significant (p <0.001). The score (Mean + SD) of all domains’ of SF-36 in both the studied groups were also significantly different. In this SLE series significant correlation (R - + 0.390, p 0.001) was observed between HAQ score and FMTP. And significant correlation was also observed almost in all domains of SF-36 with FMTP. Health status in SLE patients was poor in those who have higher number of FMTP count. Health status was more reflective by SF-36 in comparison to HAQ. JCMCTA 2015 ; 26 (2) : 44 - 52